PENDAPATAN PEKERJA WANITA PADA INDUSTRI PENGOLAHAN SKALA BESAR - Gunawan Wibisono; Sukamdi Sukamdi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1995)
Labor income is a very important issue in the process of industrialization in developing countries. Most strikes and labor conflicts in the last three years were based on workers' desire to increase income. Regarding the fact that most laborers have poor education one common means of increasing income is by lengthening work hours. The results of this study tend to prove this statement. However, this strategy has only increased total income, not real income. Income per hour does not change, and even decreases. It means that extending working hours has only increased self-exploitation. Inaddition, this result has an important implication on the analysis of labor utilization. Laborers who are fully utilized do notal ways have a higher income than those underemployed. Therefore underemployment by working hours does not represent the real labor force problem.